Derrida after the end of writing : political theology and new materialism - Crockett, Clayton, 1969- (Perspectives in continental philosophy., 2018)
This book offers a new materialist interpretation of Derrida's later work, including his engagements with religion and politics. It argues that there is a shift from a context or background motor scheme of writing to what Derrida calls the machinic, and Catherine Malabou calls plasticity.